Synthesis of microwave-assisted poly(methyl vinyl ether-co-maleic anhydride)-bovine serum albumin bioconjugates - Karahan, Mesut; Tuglu, Sevecen; Mustafaeva, Zeynep (INFORMA HEALTHCARE, 2012)
The water-soluble poly(methyl vinyl ether-co-maleic anhydride) copolymer-bovine serum albumin bioconjugates were synthesized in the presence of 1-ethyl-3-(3-dimetilaminopropyl) carbodiimide hydrochloride as cross-linking agents via microwave-assisted and conventional methods and characterized by size-exclusion chromatography and high-performance liquid chromatography. According to size-exclusion chromatography and high-performance liquid chromatography results, the bioconjugates synthesized in the microwave-assisted method are more stable and efficient than the conventional method. The reaction time is shortened from 17 hours to 15 minutes by means of the microwave-assisted method.
Keywords: Polyelectrolyte; protein; water soluble bioconjugate; microwave-assisted; PERFORMANCE LIQUID-CHROMATOGRAPHY; WATER-SOLUBLE COMPLEXES; POTENTIOMETRIC TITRATION; LIGHT-SCATTERING; ACID; COPOLYMERS; POLYMERS; Biotechnology & Applied Microbiology; Engineering; Materials Science